Information communication technology, knowledge management, job and customer satisfaction: a study of healthcare workers in Lebanon - Epaminonda, Epaminondas; Chaanine, Johnny; Vrontis, Demetris; Thrassou, Alkis; Christofi, Michael (My University, 2020)
Purpose: The paper aims to identify, analyze and discuss the links between information and communications technology (ICT) and knowledge management (KM), on the one hand, and job satisfaction (JS) and customer satisfaction (CSAT), on the other hand, in hospitals in Lebanon. Design/methodology/approach: A mixed-methods approach has been adopted that utilizes both quantitative and qualitative primary data, along with supportive and peripheral secondary ones. Specifically, a survey measuring variables was conducted among health-care professionals, with whom interviews were also conducted for greater depth and to refine the findings and relationships under study. Findings: The results of the quantitative study find no statistically significant relationships between the variables. The qualitative study suggests that this is likely because of the subjectivity of the evaluations and/or their mutual canceling. This is further partly explained not only through technical/functional deficiencies of the system but also through the impact of implicit and peripheral forces, adjacent to contextual aspects. Originality/value: The research adds significant and focused knowledge on the subject of the linkage of ICT and KM with JS and CSAT, in the context of emerging economies.
Keywords: Customer satisfaction; Health care; Hospitals; Information and communications technology; Job satisfaction; Knowledge management; Lebanon